Livestock practices, use of digital tools and co-design and flow of information: Brazil baseline assessment in the region of Novo Repartimento (Pará State, Brazil) - Costa, Ciniro; Suber, Marta; Dittmer, Kyle Michael; Miccolis, Andrew; Terra, Maya; Oliveira, Denis; Lima, Paulo; Laurens, Violaine (Bioversity International and the International Center for Tropical Agriculture, 2022)
Aiming to evaluate the status of key agroecological and digital ecosystem aspects, this report presents a study on major livestock practices, the use of digital tools, and the flow of information that have been carried out among actors working in the region of Novo Repartimento, Anapú and Pacajá (Para-Brazil), whereby ATDT project plans to implement its year 2 activities (2023) in partnership with Solidaridad. This study was based on a previous assessment done by the Agroecological TRANSITIONS program’s Inclusive Digital Tools to Enable Climate-informed Agroecological Transitions (ATDT) Brazil implementation partner (Solidaridad) on farmer’s profile, the status of livestock practices adoption and use of digital tools of about 1,000 smallholders in the target region. A field activity was deployed to visit and interview a sample of Solidaridad’s extension agents (n=13) and farmers supported by Solidaridad (n=15) working in the region.